Endovascular Treatment With and Without Intravenous Thrombolysis in Large Vessel Occlusions Stroke: A Systematic Review and Meta-Analysis - Li, Shuo; Liu, Dan-Dan; Lu, Guo; Liu, Yun; Zhou, Jun-Shan; Deng, Qi-Wen; Yan, Fu-Ling (Frontiers in Neurology, 2021)
Background Previous studies have shown conflicting results about the benefits of pretreatment with intravenous thrombolysis before endovascular treatment (EVT) in patients with acute ischemic stroke (AIS) with large vessel occlusions (LVOs). This study aimed to investigate the clinical efficacy and safety of EVT alone versus bridging therapy (BT) in patients with AIS with LVOs. Methods A systematic review with meta-analysis of all available studies comparing clinical outcomes between BT and EVT alone was conducted by searching the National Center for Biotechnology Information/National Library of Medicine PubMed and Web of Science databases for relevant literature from database inception to October 20, 2020. Results A total of 93 studies enrolling 45,190 patients were included in the present analysis. In both unadjusted and adjusted analyses, BT was associated with a higher likelihood of 90-day good outcome (crude odds ratio [cOR] 1.361, 95% confidence interval [CI] 1.234-1.502 and adjusted OR [aOR] 1.369, 95%CI 1.217-1.540) and successful reperfusion (cOR 1.271, 95%CI 1.149-1.406 and aOR 1.267, 95%CI 1.095-1.465) and lower odds of 90-day mortality (cOR 0.619, 95%CI 0.560-0.684 and aOR 0.718, 95%CI 0.594-0.868) than EVT alone. The two groups did not differ in the occurrence of symptomatic intracranial hemorrhage (sICH) (cOR 1.062, 95%CI 0.915-1.232 and aOR 1.20, 95%CI 0.95-1.47), 24-h early recovery (cOR 1.306, 95%CI 0.906-1.881 and aOR 1.46, 95%CI 0.46-2.19) and number of thrombectomy device passes ≤2 (aOR 1.466, 95%CI 0.983-2.185) after sensitivity analyses and adjustment for publication bias. Conclusions BT provides more benefits than EVT alone in terms of clinical functional outcomes without compromising safety in AIS patients with LVOs.